OSTEOARTICULAR INJURY IN PSORIATIC PATIENTS ACCORDING TO THE DATA OF PEST (PSORIASIS EPIDEMIOLOGY SCREENING TOOL) QUESTIONNAIRE AND RHEUMATOLOGICAL CLINICOINSTRUMENTAL EXAMINATION - M. N. Chamurlieva; E. Yu. Loginova; T. V. Korotaeva; E. A. Batkaev (Научно-практическая ревматология)
Objective: to estimate the prevalence of psoriatic arthritis (PsA) and the pattern of osteoarticular injury in psoriatic patients according to the data of the PEST (Psoriasis Epidemiology Screening Tool) questionnaire.Subjects and methods. The trial included 80 psoriatic patients who had sought for dermatological and rheumatological advice (35 men and 45 women); mean age 43.06±1.71 years; psoriatic skin damage area (PSDA) 9.83±2.63%; and psoriasis area severity index (PASI) 12.05±3.23; dermatology life quality index (DQLI) 8.57±0.94. Answers to 6 questions about nail psoriasis in the PEST questionnaire were rated; each positive answer corresponded to 1; PEST ≥3 or <3 is indicative of the presence or absence of psoriasis, respectively. All patients, irrespectively of PEST value, were examined by a rheumatologist and underwent a standard clinicoinstrumental examination. The CASPAR criteria were considered to be a gold standard of PsA diagnosis.Results. 53 (66.2%) patients had PEST≥3; the CASPAR criteria confirmed PsA in 40 (75.4%) of them. 27 (33.8%) patients had PEST<3; in 13 (48%) of them, fulfilled CASPAR criteria. PsA was first diagnosed in 30 (56.6%) of the 53 patients. Thus, PsA was identified in 53 (66.2%) of the 80 patients; another rheumatic disease (RD), such as dermatomyositis, rheumatic polymyalgia, osteoarthritis, ankylosing spondylitis, reactive arthritis, rheumatoid arthritis (RA), gout, etc., was found in 10 (12.5%); a concurrence of RDs (RA and gout) in 3 (3.7%); RD was absent in 14 (17.5%) cases. The disease duration was <1 year in 17 (34%) of the 53 patients with PsA, 1 to 2 years in 16 (32%), 2 to 3 years in 11 (22%), and ≥3 years in 9 (18%). Nail psoriasis was detected in 55 (70%) patients. It was found in 38 (71.7%) patients with PsA and in 17 without this disease. In patients with PsA, PSDA averaged 7.23±2.24%; PASI 11.69±1.94; DQLI 7.71±0.17, respectively; in those without PsA 11.44±2.78%, 14.94±4.29, and 8.96±1.74, respectively. No significant differences of these parameters were found.Conclusion. Thus, in psoriasis, there may be any RD, chiefly PsA with common nail involvement. The PEST questionnaire reveals PsA at its early stage in the majority of cases; however, its isolated use is not sufficient to establish accurate diagnosis and rheumatologic clinicoinstrumental examination is necessary.